Mpox knowledge and vaccination hesitancy among healthcare workers in Beijing, China: A cross-sectional survey - Yuan Yang; Weijie Zhang; Baihui Han; Han Meng; Jiaqi Wang; Ke Wu; Leiwen Fu; Bingyi Wang; Xiaohong Jiang; Qian Li; Zhiyuan Xu; Ye Zhang; et al. (Vaccine: X, 2024)
Background: Mpox, one of the most serious threats to global health, is now being seen in small but rising numbers in Beijing, China. Our study aimed to investigate healthcare workers’ (HCWs) knowledge of Mpox and to explore reasons associated with their hesitancy to vaccinate against Mpox in Beijing, China. Methods: A cross-sectional study was conducted among HCWs in Beijing from July 24 to August 2, 2023, through an online questionnaire. Participants answered questions about sociodemographic characteristics, Mpox information sources, Mpox knowledge, perception of vaccines, and attitudes toward Mpox vaccination. We used Chi-squared test to compare difference in Mpox vaccination hesitancy between different groups. Multivariable logistic regression models were applied to analyze correlates of vaccination hesitancy among HCWs. Results: A total of 2331 HCWs completed the questionnaire, with an effective response rate of 92.45 % (2155/2331). Most of the HCWs in this study worked at tertiary hospitals (89.65 %), with a mean age of 36.69 ± 9.08 years. Among the 2155 participants, 52.99 % had over ten years of working experience, and 16.66 % were from high-risk departments relevant to Mpox treatment. Approximately 84.41 % knew about Mpox before this study, 80.79 % exhibited a high level of knowledge about Mpox, whereas 42.37 % were hesitant to be vaccinated against Mpox. Moreover, the hesitancy rate of HCWs in high-risk departments (47.91 %) was higher than in lower-risk departments (41.26 %). Higher educational level (aOR = 1.75, 95 %CI: 1.17–2.62), longer working years (1.71, 1.32–2.22), working at high-risk departments (1.34, 1.05–1.71), and lower level of knowledge about Mpox (1.78, 1.13–2.85) appeared as the most significant determinants of Mpox vaccination hesitancy among HCWs who knew about Mpox. For the HCWs who did not know about Mpox, longer working years (1.96, 1.02–3.78) were significant factors associated with their hesitancy. The predominant reason for hesitancy toward Mpox vaccination among HCWs encompassed apprehensions about vaccine side effects. Conclusion: HCWs had good knowledge of Mpox, whereas their Mpox vaccination hesitancy was also relatively high in Beijing, China. Increasing HCWs’ vaccination confidence and knowledge level about Mpox, especially for those working in high-risk departments, may be an essential way of reducing their hesitancy.